Who Are We Measuring? Teacher Effects in Gifted and Talented Teacher Rating Scales - D. Betsy McCoach; Scott Peters
Teacher rating scales (TRS) often play a part in service eligibility decisions for gifted services. Although schools regularly use TRS to identify gifted students either as part of an informal nomination process or through behavioral rating scales, there is little research documenting the between-teacher variance in teacher ratings and the consequences of such rater dependence. To evaluate the possible benefits or disadvantages of using TRS as part of a gifted identification process, we examined the student-, teacher-, and school-level variance in TRS, controlling for student ability and achievement to determine the unique information, consistency, and potential bias in TRS. Between 10% and 25% of a students$1 (BTRS score can be attributed to the teacher doing the rating, and between-teacher standard deviations represent an effect size of one-third to one-half standard deviation. Our results suggest that TRS are not easily comparable across teachers, making it impossible to set a cut score for admission into a program (or for further screening) that functions equitably across teachers.s